Ethanol fermentation of sago pith - Chang, Hua Ing. (Universiti Malaysia Sarawak (UNIMAS), 2009)
In this study, wet sago starch extracted from the grounded fresh sago pith was used as the carbon source in enzymatic hydrolysis to produce glucose and subsequently used for ethanol fermentation. Exactly 500g of sago pith was added with three disti)Jed water at 500ml, 1000ml, and 1500ml. Starch extracted from the di fferent vol urnes sago slurry were 34.0 I giL, 29.99g1L and 27.97g1L respectively. The degree of enzymatic hydrolysis among the three variable samples was similar, in which 103.20%, 99.54% and 97.07% respectively. Glucose concentration produced were 35. \OglL, 29.85g1L and 27.15gfL for 500ml, 1000mi and 1500ml disti )Jed water added to the pith sample. It was confirmed that glucose from hydrolyzed wet sago starch is fermentable (92.85% of fermentation efficiency) and potentia)Jy applicable as substrate for ethanol fermentation. A kilogram of fresh sago pith added with 1 L of water (I: I dilution) able to extract 68.02g1L of wet starch, 70.21 giL glucose and 33.57g1L ofethanol.